'I love Alaska': posthuman subjectivity and memory on the final frontier of our ecological crisis. Issue 5 (29th July 2017) - Groes, Sebastian
ABSTRACT: This essay looks at recent representations of the US state of Alaska to consider how climate change is altering our understanding of the twenty-first-century human mind, and, more specifically, memory. Caught up in the scramble for the Arctic, Alaska is directly affected by climate change, but the state's vastness also forms a metaphor for the tremendous challenges our ecological crisis puts before us: the sublime landscape forms an Anthropocenic archive of human activity, and its scalar vastness and unmappability challenge human imagination. This essay questions the rhetorical utopianism and idealism about the planetary consciousness apparently generated by new technology, showing that art and literature argue for a sober, pragmatic approach to our crisis in scaling up our imagination. After tracing traditional Alaskan mythologies, I show how contemporary eco-memoirs test and challenge humanist dogmas. The Big Data project, I Love Alaska, and the cinematographic exploration of AI and human evolution, Ex Machina, also point beyond humanism and posit Alaska as a potent imaginary space where anti-anthropocentric ideas, the changing relationship between humans and nature, and the potential of a planetary consciousness/memory can be explored. Both paths demand posthuman subjectivities that stretch, or perhaps overstretch, the limits of the human imagination.